Aplikasi Pupuk Kotoran Kelinci Dan Pupuk Anorganik Pada Tanaman Jagung Pulut (Zea Mays Ceratina L.) - ; Fitriyah, Nur; D Andayani, Retno; Handayani, Tri; Novitasari, Dian (JURNAL ILMIAH AGRINECA, 2024)
The aim of the research was to determine the effect of rabbit manure application on the growth and yield of pulut corn, to determine the correct NPK dose on the growth and yield of pulut corn. The research was carried out from February to July 2023. The research was carried out at the UNISKA Integrated Field Laboratory, Rejomulyo Village, Kediri City District, with an altitude of 67 meters above sea level. The average temperature in the morning is 27.22? and in the afternoon 34.36? with average humidity in the morning 86.07 and in the afternoon 49.32. Sandy loam soil type with an acidity level of 6.7 pH. Using a factorial randomized block design (RAK) with two factors. The first factor consists of two levels of rabbit manure treatment, namely, K1 = solid rabbit manure (3.5 kg/plot) and K2 = liquid rabbit manure (40 ml/plant). The second factor is the dose of NPK fertilizer with 4 levels of treatment, namely, N0 = NPK fertilizer dose 0 gr/plant, N1 = NPK fertilizer dose 3 gr/plant, N2 = NPK fertilizer dose 6 gr/plant, N3 = NPK fertilizer dose 7 gr/plant . The data obtained from the observations were entered into a table for the F test using the variance analysis method and further tested using the 5% BNT test. Based on the research results, there was no interaction between rabbit manure treatment and the dose of NPK fertilizer on the growth and yield of pulut corn. Each treatment of rabbit manure and dose of NPK fertilizer showed a significant effect on the growth and yield of pulut corn. Rabbit litter treatment had a significant effect on the variables number of leaves, plant height and stem diameter. The dose of NPK fertilizer has a real influence on the number of leaves, plant height, stem diameter, ear length, ear diameter. The best cob weight without husks was shown in the NPK fertilizer treatment of 9 gr/plant.